High Prevalence of Hypovitaminosis D in Adolescents Attending a Reference Centre for the Treatment of Obesity in Switzerland - Pollyanna Patriota; Sylvie Borloz; Inge Ruiz; Thérèse Bouthors; Serge Rezzi; Pedro Marques-Vidal; Michael Hauschild (MDPI AG, 2022)
Background: Hypovitaminosis D is common in populations with obesity. This study aimed at assessing (1) the prevalence of hypovitaminosis D and (2) the associations between vitamin D levels and cardiovascular risk factors in adolescents attending a reference centre for the treatment of obesity. Design: Cross-sectional pilot study conducted in the paediatric obesity unit of the Lausanne university hospital, Switzerland. Methods: Participants were considered eligible if they (1) were aged between 10 to 16.9 years and (2) consulted between 2017 and 2021. Participants were excluded if (1) they lacked vitamin D measurements or (2) the vitamin D measurement was performed one month after the base anthropometric assessment. Hypovitaminosis D was considered if the vitamin D level was <30 ng/mL (<75 nmol/L). Severe obesity was defined as a BMI z-score > 3 SD. Results: We included 52 adolescents (31% girls, mean age 13 ± 2 years, 33% with severe obesity). The prevalence of hypovitaminosis D was 87.5% in girls and 88.9% in boys. The vitamin D levels were inversely associated with BMI, Spearman r and 95% CI: −0.286 (−0.555; −0.017), p = 0.037; they were not associated with the BMI z-score: −0.052 (−0.327; 0.224), p = 0.713. The vitamin D levels were negatively associated with the parathormone levels (−0.353 (−0.667; −0.039), p = 0.028) and positively associated with the calcium levels (0.385 (0.061; 0.708), p = 0.020), while no association was found between vitamin D levels and blood pressure and lipid or glucose levels. Conclusion: almost 9 out of 10 adolescents with obesity in our cohort presented with hypovitaminosis D. Hypovitaminosis D does not seem to be associated with a higher cardiovascular risk profile in this group.